The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1111/j.1365-2486.2009.02132.x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence for the attenuating effect of SOM protection on temperature sensitivity of SOM decomposition

Abstract: The ability to predict C cycle responses to temperature changes depends on the accurate representation of temperature sensitivity (Q 10 ) of soil organic matter (SOM) decomposition in C models for different C pools and soil depths. Theoretically, Q 10 of SOM decomposition is determined by SOM quality and availability (referred to here as SOM protection). Here, we focus on the role of SOM protection in attenuating the intrinsic, SOM quality dependent Q 10 . To assess the separate effects of SOM quality and prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
69
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(80 citation statements)
references
References 51 publications
6
69
2
Order By: Relevance
“…First, the physical protection of SOC due to aggregation or association with soil minerals tends to increase with depth (Kögel-Knabner et al 2008;Schrumpf et al 2013), which may lead to a physical disconnect between microbes and substrates and a lower temperature dependence of microbial respiration in subsoils (Gillabel et al 2010;Conant et al 2011). Although physical protection of SOC was not directly measured in this study, MBC and total N contents may indicate the intensity of physical protection of SOC for microbial decomposition.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…First, the physical protection of SOC due to aggregation or association with soil minerals tends to increase with depth (Kögel-Knabner et al 2008;Schrumpf et al 2013), which may lead to a physical disconnect between microbes and substrates and a lower temperature dependence of microbial respiration in subsoils (Gillabel et al 2010;Conant et al 2011). Although physical protection of SOC was not directly measured in this study, MBC and total N contents may indicate the intensity of physical protection of SOC for microbial decomposition.…”
Section: Discussionmentioning
confidence: 79%
“…However, previous studies have shown inconsistent patterns of Q 10 values of soil respiration with soil depth. Increase (Lomander et al 1998;Fierer et al 2003;Jin et al 2008;Karhu et al 2010), decrease (Winkler et al 1996;MacDonald et al 1999;Gillabel et al 2010), or no changes (Fang et al 2005;Leifeld and Fuhrer 2005;Rey et al 2008) in apparent Q 10 values with increasing soil depth have been observed in different studies. Much of the variation in the apparent temperature sensitivity of SOC decomposition may be related to the fact that labile substrate availability is often unaccounted for in these studies Gershenson et al 2009;Conant et al 2011).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Their application specifically highlights the role of extracellular enzymes during decomposition and how these constraints will further affect the release of soil organic matter as a consequence of warming. While microbial decomposition models are able to improve prediction of organic carbon stock globally and can successfully recreate litter decomposition dynamics, the long-term trajectory of a warming response needs further evaluation Hararuk et al, 2015). In particular, a positive feedback between depolymerisation and microbes can only be curbed via the longer-term adjustment of soil organic matter and therefore lead to oscillation in both microbial biomass and soil organic matter .…”
Section: Discussionmentioning
confidence: 99%